2020
DOI: 10.3390/nu13010066
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Low Glycemic Index Mediterranean Diet: Main and Modification Effects on NAFLD Score. Results from a Randomized Clinical Trial

Abstract: Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common chronic liver disease worldwide, and lifestyle modification is the current standard treatment. The aim of the study was to estimate the effect of two different physical activity (PA) programs, a Low Glycemic Index Mediterranean Diet (LGIMD), and their combined effect on the NAFLD score as measured by FibroScan®. Methods: Moderate or severe NAFLD subjects (n = 144) were randomly assigned to six intervention arms during three months. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…The impact of doing physical activity and following a Mediterranean diet on NAFLD has been widely studied in recent years [48][49][50][51]. At the same time, the relevance of psychological biomarkers has also been recently proven in NAFLD [24,52].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of doing physical activity and following a Mediterranean diet on NAFLD has been widely studied in recent years [48][49][50][51]. At the same time, the relevance of psychological biomarkers has also been recently proven in NAFLD [24,52].…”
Section: Discussionmentioning
confidence: 99%
“…Reassuringly, in a large Chinese population, an RRR-derived DP related to inflammatory markers is also characterized by high intakes of sugar-containing foods and positively associated with NAFLD [30]. In fact, low glycemic index diets are currently promoted for the amelioration of NAFLD [31].…”
Section: Dietary Patterns and Proxy Markers Of Nalfd And T2dmmentioning
confidence: 99%
“…Correct dietary habits are important for the regulation of cell membrane in the liver, considered an organ leader in maintaining lipid balance. The combination of diet and physical activity has been considered effective in the prevention of NAFLD [139], so that, clinical studies have demonstrated that both the aerobic and a resistance exercise program physical activity, alone or combined, are capable of reducing NAFLD scores [140,141].…”
Section: Nafld and Lifestyle Interventionsmentioning
confidence: 99%